2006
DOI: 10.1007/s00125-006-0532-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum calcium is independently associated with insulin sensitivity measured with euglycaemic–hyperinsulinaemic clamp in a community-based cohort

Abstract: Aims/hypothesis Diabetes mellitus type 2 is associated with altered calcium metabolism. Moreover, in diseases with supranormal serum calcium levels, such as primary hyperparathyroidism, the prevalence of diabetes is increased. Relatively little is known about the relationship between serum calcium concentration and the underlying causes of diabetes-insulin resistance and defective insulin secretionin the normocalcaemic general population. Materials and methods We investigated associations between serum calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
49
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 36 publications
6
49
0
2
Order By: Relevance
“…Increasing intracellular calcium levels have been shown to decrease the effect of insulin in adipocytes due to reduced number of glucose transporters (GLUT4) and decreased insulin receptor activity (5,7). The dietary intake of calcium did not seem to influence insulin sensitivity (4).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Increasing intracellular calcium levels have been shown to decrease the effect of insulin in adipocytes due to reduced number of glucose transporters (GLUT4) and decreased insulin receptor activity (5,7). The dietary intake of calcium did not seem to influence insulin sensitivity (4).…”
Section: Introductionmentioning
confidence: 79%
“…Previous reports have shown that patients with diabetes have elevated serum calcium levels compared with non-diabetic individuals (3), and this has mainly been linked to impaired insulin sensitivity rather than defective insulin secretion (4). In diseases with markedly elevated serum calcium, such as primary hyperparathyroidism, there is a two-to four-fold higher prevalence of type 2 diabetes and glucose intolerance compared with the general population (5).…”
Section: Introductionmentioning
confidence: 99%
“…It is easy to infer that dysregulation of Ca 2ϩ homeostasis could have a pronounced disturbing effect on insulin-stimulated glucose disposal and mitochondrial function. Abnormal Ca 2ϩ homeostasis has been reported in skeletal muscle of patients with type 2 diabetes (47), and more recently, serum calcium was demonstrated to be independently associated with insulin resistance measured with euglycemic-hyperinsulinemic clamp (48). Although similar abnormalities in muscle transcripts of calcium pathway genes were not reported in studies of patients with type 2 diabetes (20 -22), it is too early to conclude that the observed changes should play a unique role for insulin resistance in skeletal muscle of PCOS subjects.…”
Section: Discussionmentioning
confidence: 98%
“…In T2DM subjects, calcium levels have been shown to be higher (10, 13) and associated with fasting glucose or insulin resistance (8,9,12); conversely, other studies have reported no relationship with markers of glucose control (15), insulin resistance (7), or insulin secretion (7,9).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, crosssectional and case-control studies investigating the relationship between calcium homeostasis and glucose metabolism have reported conflicting results (7)(8)(9)(10)(11)(12)(13)(14)(15); however, only a few studies have prospectively evaluated the association between serum calcium and risk of incident T2DM, suggesting that higher levels of serum calcium predict an increased risk of T2DM (16)(17)(18). These studies have relied either on total serum calcium or the indirect, albumincorrected estimate of serum calcium: these measurements, however, only approximate the levels biological-active serum calcium (iCa) (19).…”
Section: Introductionmentioning
confidence: 99%